2015
DOI: 10.1016/j.kjms.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial indicators related to neuroticism in both sexes: A study of incoming university students

Abstract: Neuroticism may have great impact on mental and physical health in both sexes. The aims of this study were to explore whether relationships between neuroticism scores and psychosocial indicators as well as metabolic syndrome in a population of incoming university students existed in the different sexes. In total, 4266 incoming students were included in this study. The test battery comprised a self-administered structured questionnaire, including the neuroticism subscale of the Maudsley Personality Inventory, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In general, Neuroticism (Dong et al, 2012;Floros et al, 2014;Tsai et al, 2009), Impulsivity (Dalbudak et al, 2013;Floros et al, 2014) and Psychoticism (Dong et al, 2012) were significant predictors of IA. Moreover, in group comparisons with college students, groups composed by people with high scores in IA obtained higher means in these pathological personality traits when compared with groups with low scores in IA (Chang et al, 2015;Senormanci et al, 2014;Tsai et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In general, Neuroticism (Dong et al, 2012;Floros et al, 2014;Tsai et al, 2009), Impulsivity (Dalbudak et al, 2013;Floros et al, 2014) and Psychoticism (Dong et al, 2012) were significant predictors of IA. Moreover, in group comparisons with college students, groups composed by people with high scores in IA obtained higher means in these pathological personality traits when compared with groups with low scores in IA (Chang et al, 2015;Senormanci et al, 2014;Tsai et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…Altogether, the results reported in the studies indicated the relationship between IA and Neuroticism, Impulsivity, Psychoticism, and PDs. IA was positively correlated to Neuroticism (Chang et al, 2015 BPDFS: Borderline Personality Disorder Features Scale; a: rehabilitation centers; b: diagnostic of IA; c: diagnostic of alcohol dependence; d: registered in the volunteer service for counseling students with problematic internet use and with diagnostic of IA; e: in this study the Dissociative Experiences Scales was used to screening symptoms of Dissociative Identity Disorder (DID); we did not used these results as DID is not considered as a PD in the diagnostic manual (APA, 2013); f: in this study the Dysfunctional Attitudes Scale was used to screening dysfunctional attitudes and beliefs, the back depression inventory was used to measuring symptoms of depression and Rosenberg Self-Esteem Scale was used to measure global feelings of self-worth or self-acceptance; these results were not presented in our study as it´s not relevant to our goal; g: sample specificities (e.g., patient, students, etc.) were not given; h: cut-off from Neuroticism scale of the Maudsley Personality Inventory was used to establishment of groups; i: PD diagnostic based on DSM-IV; j: narcissistic, borderline, obsessive compulsive, schizotypal and antisocial; k: subscales: impulsiveness, neuroticism-anxiety, sensation seeking, aggression-hostility, activity, and sociability.…”
Section: Study Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, about 46% of college students reported having poor sleep quality in the England [4]; In German, 48.9% university students reported having underwent poor sleep quality [5]; similarly, the incidence of poor sleep quality among Chinese freshmen is higher, ranging from approximately 31.0% and 43.28% [6,7]. Poor sleep quality not only damages physical health such as obesity [8], type 1 diabetes [9], and cardiovascular disease [10]; but also contributes to a number of negative mental health outcomes such as depression [11], anxiety [12], attention de cit [13], and negative personality traits [14]. Therefore, exploring positive and effective methods are crucial to prevent poor sleep quality among college students.…”
Section: Introductionmentioning
confidence: 99%
“…For example, neuroticism, a personality trait indicative of emotional stability, peaks especially in late adolescence and gradually diminishes over adulthood. This trait has been shown to negatively correlate with quality of life and can be a predictor of quality-of-life outcomes ( 21 , 22 ).…”
mentioning
confidence: 99%